“ 美人魚”男嬰事件之我見: A Case Study of a "Mermaid Baby" - SUN, Yingmei (International Journal of Chinese & Comparative Philosophy of Medicine, 2008)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 2006 年底湖南省兒童醫院救治了一名“美人魚”男嬰。儘管醫務人員日夜奮戰，但這個不幸的嬰兒仍然不治夭折，醫院為此付出巨大的代價。本文從儒家觀點出發，就此事件闡述個人見解：不贊成醫院實施原本就希望渺茫的搶救行為，主張為“美人魚”男嬰提供臨終關懷照護直至其安逸、無痛苦地離去，將節省的醫療衞生資源，用於更多能夠治癒患者的有效治療上；針對“中國實際每年的出生缺陷患兒大約有50 萬-60 萬” 1 的嚴酷現實，闡明人與自然和諧相處的必要性與緊迫性。 “Mermaid” syndrome is a rare medical condition in which an infant is born with his/her legs fused together from trunk to heels.“ Mermaid” syndrome is almost always fatal within days of birth due to serious defects in vital organs and complications associated with abnormal kidney and bladder development. In 2006 a male baby with a“ mermaid” syndrome was born in the Hunan Provincial Children’s Hospital in central China. Doctors tried to keep the baby alive with all kinds of means, even though the baby had a slim chance to survive. The case gives rise to a heated debate concerning the bioethical issues such as the quality of life, right to life, health disparities, the distribution of medical resources, and the practice of euthanasia. In this paper, I shall discuss the ethical dilemma involved in the case of the“ Mermaid Baby.” I ask the question whether it can be justified to save the life of the little baby, acknowledging that he could die at any time and the quality of his life was low even if he could survive. Some media criticized the hospital for making a scene while other blame that the hospital abused the medical resources that could be better used for saving life of many other babies who badly need medical treatment and have better chances to survive. Meanwhile, I shall turn to traditional moral systems, particularly Confucianism for alternative solutions. The paper concludes that environmental protection is the real issue given that there are about fifty to sixty thousand babies with birth defects every year in China. DOWNLOAD HISTORY | This article has been downloaded 31 times in Digital Commons before migrating into this platform.